Trajectory Tracking Control Design for Mobile Robot Using Interval Type-2 Fuzzy Logic - Akmal, Mochammad Dekcy; Al Tahtawi, Adnan Rafi; Wijayanto, Kartono; Wahab, Faisal (Journal of Fuzzy Systems and Control, 2024)
A two-wheeled mobile robot (TWMR) is a type of mobile robot that is widely used for several tasks, one of which is trajectory tracking. This task will be complicated for the robot to track the desired trajectory when there are disturbances in the robot, such as the presence of noise from the sensor feedback. Therefore, a robust control mechanism is needed so that the robot is able to track the trajectory properly. This study proposes an Interval Type-2 Fuzzy Logic Control (IT2FLC) for controlling TWMR which has noise parameters in the heading angle. IT2FLC Sugeno method is designed with error input from the heading angel and its changes, while the output is a voltage for the left and right motors of the robot. The input membership function is constructed using a triangular function with three different Footprint of Uncertainty (FoU) values as a comparison. This controller is then implemented to control the heading angle according to the trajectory of the robot using the Differential Drive Wheeled Mobile Robot (DDWMR) kinematic model. Several scenarios are then testing via MATLAB/Simulink to see the controller performance. The test results by including the noise parameter as disturbance show that IT2FLC can produce a better performance when compared to ordinary FLC. The widest FoU value of 0.3 can produce the smallest error value of up to 0.003 on the ISE criteria.